PROSPECTS OF NEWLY DISCOVERED UGUR AREA IN THE NORTHWEST OF THE GEDABEY ORE DISTRICT (LESSER CAUCASUS, AZERBAIJAN) - Imamverdiyev, N.; Baba-zadeh, V.; Mursalov, S.; Valiyev, A.; Mansurov, M.; Ismayilova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article describes Ugur exploration area located in Gedabey Ore District of the Lesser Caucasus in NW of Azerbaijan. Results of trenches and channels sampling on the surface, RC bore holes and summary of significant drill intercepts (>0.29 ppm Au) of Ugur Exploration area are presented. It has been established that The deposit is enlarged by highly gold-silver result of surface outcrop rock chip samples over an area of 2.5 kms North-South by 2 kms East-West, with the Reza gold deposit located in the central part. Out of metallic minerals crystalline hematite was observed. On surface intensive barite and barite-hematite vein and veinlets, also gossan zones were observed. The main mineralization zones have been sampled in three trenches at a distance up to 270 m by trenches #1, #2 and #3 and received positive results for gold and silver. Also there have taken approximately 550 samples from outcrop #1 and #2. On the main orebody at surface centre there occured secondary quartzites with vein-veinlets barite-hematite mineralization over which there remain accumulations of hydrous ferric oxides cementing breccias of quartz and quartzites. And in erosion parts "reddish mass" being oxidation product of stock and stockverk hematite ores were observed. Representing typical gossans, these accumulations by the data of trenches for thickness about 5-10 m contain gold 0.3-2.0 ppm and silver 1.0-15.0 ppm. Ten diamond drill holes, named UGDD 01-10 were drilled in the center part of the deposit. The drill holes were sampled mainly in 1 meter lengths from the top of the hole to the bottom. The core samples were marked and placed into standard boxes. Significant intervals of weighted averages greater than 0.29 ppm over down hole intervals of 1 metres or greater (>0.29 ppm Au and >0.9 m) are summarized in table 3 below. In conclusion, the outcropping alteration at the deposit is typical of the upper steam-heated levels of high-sulfidation epithermal (HSE) deposits, which in most mineralized systems of this type, may cap higher-grade gold mineralization which is hosted by underlying vuggy and oxide zones.